(untitled) (Research, Society and Development, 2022)
This article aims to investigate the possible contributions that the implementation of theater in school activities can help in the preservation of culture in schools with students belonging to quilombola communities. It addresses the main public educational policies in Brazil and their contributions to the quilombola communities in the country. Whether in the pedagogical aspect or in the artistic aspect, watched or staged, theater proves to be an important tool to be inserted in the school curriculum due to the ability that it helps during the process of children’s formation. This research seeks to explain the importance of inserting theater in the curriculum in quilombola schools, aiming at the preservation of their culture. For the accomplishment of this work, scientific articles, laws and decrees related to the theme were analyzed. In the final considerations, the importance of the insertion of theater in quilombola schools is highlighted due to the contributions that theater makes possible in the process of skills development, learning and in the process of presentation and preservation of culture based on their values, their customs and their territoriality.